MARCAJE DE CAMPONOTUS MOROSUS SMITH , 1858 (HYMENOPTERA : FORMICIDAE ) SEGUN LA TECNICA DE FRESNEAU Y CHARPIN (Acta Entomológica Chilena, 2022)
To study ihe división of laboui in ants of the genus Caniponotus, a method of individual markingby pholography was developed following Fresnau and Charpin recommendations. Using these marksit is possiblc to check and control the activitics of individual ants.